2016
DOI: 10.1016/j.vaccine.2016.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the unreached with polio vaccine and other child survival interventions through partnership with military in Angola

Abstract: Military is a potentially productive force that can be used for any development activities in any country. The Angolan experience has demonstrated that it is possible to form a partnership with the military for basic health intervention activities with little training and investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…The findings are consonant with previous approaches to reach similar populations in other regions affected by conflict and insecurity 26, 27. Our experience provides objective evidence that it is possible to gain community trust and achieve gains in immunisation and OPV and IPV coverage using an integrated approach, and has implications for geographies facing resistance and limited community engagement.…”
Section: Discussionsupporting
confidence: 86%
“…The findings are consonant with previous approaches to reach similar populations in other regions affected by conflict and insecurity 26, 27. Our experience provides objective evidence that it is possible to gain community trust and achieve gains in immunisation and OPV and IPV coverage using an integrated approach, and has implications for geographies facing resistance and limited community engagement.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have highlighted hard to reach areas and nomadic lifestyles as major challenges for immunization [41]. Research in Angola identified vast unreachable areas due to poor infrastructure and also security [45,46]. Security remains an issue in Galkacyo District due to regular armed volatile clan clashes.…”
Section: Discussionmentioning
confidence: 99%
“…A suggestion for the use of military personnel for vaccination activities was made from the experience of insecurity in the Lake Chad region [12] but experts argued that this method should be used with caution as it can be counterproductive by deepening false perceptions regarding the vaccine [10]. However, partnership with the military was seen to improve coverage of polio vaccination among insecure and hard-to-reach areas in Angola [13]. It was also found to address some issues of vaccine hesitancy.…”
mentioning
confidence: 99%